Thermoacoustic Sandwich Panels produced with Balsawood or Pineapple Fiber as Core and Melina Wood as external Veneer - Moya Roque, Roger (2025)
His study aims to produce and assess CSP thermoacoustic insulators by examining their physical, mechanical, acoustic, and thermal characteristics. The panels, with thicknesses of 12 mm and 19 mm, are constructed using cores of balsawood or pineapple leaves (Ananas comosus) (PALF) and melina wood (Gmelina arborea) as veneer.